Hvem vil vi være? ”Africa for Norway” og den humanitære relation - Sharma, Devika (K&K - Kultur og Klasse, 2015)
In this article I examine a recurrent critique of humanitarianism and humanitarian phenomena, a critique centering on the presumably anti-political and emotionally complacent nature of such phenomena. But from which position, I ask, does it make sense to critique the humanitarian culture in which we live. In discussing these issues, I take as my point of departure the satirical campaign video Radi-Aid by the fictitious humanitarian NGO, Africa for Norway. This spoof campaign parodies humanitarian aesthetics, humanitarian emotions, as well as the stereotyping typically involved in humanitarian campaigns. Yet, for all its satirizing it does not make a clean break with the very humanitarian culture whose negative aspects it aims to expose. The criticality of the Africa for Norway initiative is thus clearly constrained, but does this imply that the satire is doomed to sheer complicity with the social dynamics it questions? My interest is these issues stems from dissatisfaction with the common notion that a relevant critique of humanitarian relations between the global North and the global South must be a critique of macro level political economy.